World histories from below disruption and dissent, 1750 to the present - Burton, Antoinette M. 1961-; Ballantyne, Tony 1972- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
"This textbook is the first to consider world history from below, providing an alternative to the privilege of Western powers and elite political structures found in conventional global history narratives"--Provided by publisher.